A Case Control Study on Serum Level of Micronutrients in Decompensated Liver Cirrhosis Patients in Mymensingh, Bangladesh - Hossain, Md Shahadath; Rahman, Md Muzibar; Shahidullah, ASM; Sen, Bina; Hoque, Md Rafiqul; Paul, Arup Ratan; Saha, Kamona Rani (Community Based Medical Journal, 2019)
Liver cirrhosis is an end stage condition of liver disease and the leading cause of death for both men and women all over the world. It causes death due to acute or chronic gastrointestinal blood loss & multi organ failure. The aim of the study is to evaluate the serum Copper, Zinc and Iron levels in patients with liver cirrhosis. A total 120 subjects were included in this study. Among them, 60 diagnosed decompensated liver cirrhosis patients denoted as case group (n=60) and 60 were normal healthy individuals denoted as control group (n=60), both the case and control groups were male because liver cirrhosis occurs rarely female in Bangladesh. The subjects were briefed and written consents were taken. Under all aseptic precaution 5 ml of venous blood was collected from median cubital vein, analysis was carried out in the Department of Biochemistry, Mymensingh Medical College, Mymensingh, over a period of one year from July 2015 to June 2016. All statistical analysis was performed by SPSS windows package, version 20. Significance of the difference between two groups were evaluated by using student's unpaired 't' test. All the values were expressed as mean ± SD and P value 0.05 was taken as the level of significance. After careful evaluation, in the present study we found significant increase in the serum Copper levels and significant decreases in the serum Zinc and Iron levels in liver cirrhosis patients when compared with that of control group. It can be concluded that to overcome fatal consequences of decompensated liver cirrhosis patients we should avoid high Copper containing food provides Zinc and Iron supplementation as well as blood transfusion may be beneficial. CBMJ 2019 July: Vol. 08 No. 02 P: 10-16